Risk factors for the development of delayed restenosis in patients with low coronary artery diameter after performed X-ray angiographic procedures - E. V. Aksenov; V. B. Golovenko (Ukrainian Journal of Cardiovascular Surgery, 2018)
The work is devoted to the study of risk factors for the development of delayed restenosis in patients with small diameter coronary arteries after performed X-ray angiographic procedures.The study included 315 patients aged 66.96±1.81 years, with a mean diameter of the true internal lumen of the arteries of 2.53±0.011 mm, which had a revascularization of the myocardium through stenting or percutaneous transluminal balloon angioplasty (PTBA).As a result of the research, it was found that there was no correlation between the development of CA restenosis and such factors as: arterial hypertension, dyslipidemia, smoking, postinfarctional cardiosclerosis (r2<0.1).In case of concomitant diabetes mellitus, restenosis of the artery in the stent was significantly more frequent (r2=0.85), while the type of diabetes did not affect the restenosis rate (r2<0.1). In such a contingent of patients, the increase in the length of the occlusion of more than 10 mm, was a reliable factor that affects the restenosis of the spacecraft in the postponed period after the stenting.The development of restenosis of the stent artery, as well as in patients who have undergone (PTBA), was not affected by such factors as: the number of affected arteries, the degree of lesion, the presence of locomotor of the stented area, involvement in the bifurcation / vascular stenosis of the vessel, the form of the atherosclerotic plaque, dissection intima arteries after «predilyatation» and implantation of the stent (r2<0,1).The following factors, such as: the presence of collateral blood flow to the procedure, the initial morphological type of occlusion, the degree and length of stenosis, the calcinosis of the vessel at the site of intervention (r2<0,01), were strongly influenced by the restenosis frequency after the stenting procedure.With the tactical features of stenting, the worst remote angiographic result of the procedure showed the use of a prosthetic smaller caliber than the lumen of the artery.